But Do They Care?: Pintrich on Motivation in Learning - Michael Fosmire (Issues in Science and Technology Librarianship)
The article discusses a paper which describes the role of student motivation in learning and teaching contexts. It outlines several factors that can affect motivation in the classroom as adapted from the paper, including self-efficacy, goal-orientation and personal and situational interest. It also explains their implications for information literacy instruction.